Pengaruh Non Perfoming Loan (NPL) dan Restrukturisasi Kredit Terhadap Profitabilitas dan BOPO pada Perusahaan Perbankan Umum Konvensional yang Terdaftar di OJK Selama Covid-19 - poernomo, harry; Winarto, Oetami P. (Business and Accounting Education Journal, 2023)
The global economy in 2020 was marked by the COVID-19 pandemic which had a tremendous impact, not only on health but also on the economy and financial system stability. The performance of banking as an intermediary institution that mobilizes funds in the economy has also been affected by the COVID-19 pandemic since early 2020. As a result of this phenomenon, the value of non-performing loans (NPLs) or non-performing loans has also decreased due to the ability to pay from customers has also decreased. The purpose of this study is to analyze and examine the effect of Non Performing Loans (NPL) and credit restructuring on the profitability and BOPO of conventional commercial banking companies registered with OJK during the Covid-19 period (June 2020 – June 2021). This type of research is quantitative research. The population of this research is all conventional general banking companies registered with the OJK during the Covid-19 period for the period June 2020-June 2021, which are 107 banks. The sampling technique in this study was purposive sampling, namely the sampling technique based on the criteria set by the researcher. The data collection technique is secondary data in the form of an annual report obtained from the OJK official website. The analytical tool to test the hypothesis uses descriptive analysis with multiple regression analysis. The results of the hypothesis test of Non Performing Loans (NPL) have a negative effect on Return on Assets (RoA), Credit Restructuring has a positive effect on Return on Assets (RoA), Non Performing Loans (NPL) have a negative effect on Return On Equity (ROE), Credit Restructuring has a negative effect on Positive effect on Return On Equity (ROe), Non Performing Loan (NPL) has a positive effect on Operating Expenses on Operating Income (BOPO), Credit Restructuring has a negative effect on Operating Expenses on Operating Income (BOPO). Based on the results of the study, it can be concluded that NPL has an effect on profitability and BOPO, while credit restructuring has no effect on profitability and BOPO. The advice given is that the author suggests that banks should better manage their productive assets by providing credit effectively, efficiently, and with the principle of prudence, because if banks can manage lending properly, it can minimize the emergence of non-performing loans (NPL).